Radical Shaming Ahead of the Aceh Regional Election: The Urgency of Religious Moderation in Instilling Ethical Values on Social Media - Dewi, Ernita; Anzaikhan, M.; Sajida Muhammad Jamil; Ramzi Murzikin (Millati: Journal of Islamic Studies and Humanities, 2025)
This article aims to analyze the phenomenon of radical shaming that has become prevalent ahead of the Aceh local elections, as well as the urgency of religious moderation in instilling ethical values on social media. Radical shaming refers to the practice of labeling certain individuals or groups as radical as a political tool to discredit them, particularly in Aceh, a region with a history of conflict and complex religious dynamics. This article falls under library research with a qualitative approach. The methodology used is descriptive analysis. The research findings conclude two main points. First, radical shaming has proven to be a tactic that exacerbates political and social polarization in Aceh, not only intensifying political competition but also undermining social cohesion. Second, the urgency of promoting ethical moderation through official institutions is crucial in preventing the spread of slander and disinformation on social media. Through a more structured and authoritative moderation approach, Aceh is expected to foster a more ethical and harmonious public sphere in the context of religion and politics.